A method for preparing sodium iron phosphate by using high-iron fly ash

CN118306961BActive Publication Date: 2026-10-20GUIZHOU MINZU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410434485.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2026-10-20
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

[0003]本发明要解决现有技术无法利用粉煤灰制备新能源电池材料的问题,进而提供一种利用高铁粉煤灰制备磷酸铁钠的方法

Benefits of technology

本发明的研究成果致力于在环保和可持续发展领域取得突破。通过巧妙地利用废弃物中的高铁粉煤灰,将其内含的铁元素转化为高纯度的硫酸亚铁铵,为新型能源磷酸铁钠电池材料的制备提供了可靠的基础。这一过程不仅实现了废弃物资源的高效再利用,还显著降低了环境污染风险。磷酸铁钠作为新能源电池的材料,具备卓越的电化学性能,包括出色的电导率和循环寿命。这不仅能够提升电池的整体性能,还有望减轻对稀有金属锂的依赖,从而在电池制造领域增加可持续性。这一创新的正极材料为电池行业的可持续发展打开了新的方向,具体如下:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118306961B_ABST
    Figure CN118306961B_ABST
Patent Text Reader

Abstract

The application relates to a method for preparing sodium iron phosphate by using high-iron fly ash, and relates to a method for preparing sodium iron phosphate. The application solves the problem that the prior art cannot prepare new energy battery materials by using fly ash. The method comprises the following steps: one, preparing ferrous ammonium sulfate; two, preparing a ferrous ammonium sulfate solution; three, preparing a Na3PO4 solution; four, dropping the ferrous ammonium sulfate solution into the Na3PO4 solution to react. The application is used for preparing sodium iron phosphate by using high-iron fly ash.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing sodium iron phosphate. Background Technology

[0002] Currently, lithium-ion batteries are the mainstream new energy battery, but they face challenges in terms of rare metal resource requirements, cost, and safety. Research on solid waste resource utilization mainly focuses on waste treatment and reuse, with relatively little research on battery material preparation. Fly ash, a waste from the coal mining industry, has some utilization pathways, but its application in battery material preparation has not been widely studied. Traditional lithium-ion batteries use limited rare metal resources such as lithium and cobalt, which are expensive and have relatively high manufacturing costs. Current solid waste resource treatment mainly focuses on reducing environmental impact, but waste may contain useful elements, failing to fully explore its potential value. Some new energy battery materials (such as sodium iron phosphate) still face challenges in charge transport speed and cycle life, affecting their performance and reliability in practical applications. Summary of the Invention

[0003] This invention aims to address the problem that existing technologies cannot utilize fly ash to prepare new energy battery materials, and thus provides a method for preparing sodium iron phosphate using high-iron fly ash.

[0004] A method for preparing sodium ferric phosphate using high-iron fly ash, comprising the following steps: 1. Mix high-speed iron fly ash with sulfuric acid, heat at 140℃~180℃ for 4h~6h, then filter and wash to obtain filtrate; ② Add sodium hydroxide solution dropwise to the filtrate to adjust the pH, and react at room temperature for 3 to 5 hours. After the reaction is complete, a reddish-brown precipitate will appear. Then filter to obtain the filter residue. ③ Add ultrapure water to the filter residue, then add sulfuric acid and iron powder. React at 60℃~80℃ for 10min~20min. Finally, filter out the excess iron powder to obtain ferrous sulfate solution. ④ Add (NH4)2SO4 to the ferrous sulfate solution to dissolve until the pH is 1~2, then evaporate and crystallize at a temperature of 90℃~110℃, and finally wash and filter to obtain ferrous ammonium sulfate. 2. Dissolve ferrous ammonium sulfate in water, then add L-ascorbic acid and stir to dissolve, thus obtaining a ferrous ammonium sulfate solution; 3. Dissolve Na3PO4 in deionized water to obtain Na3PO4 solution; 4. Add ferrous ammonium sulfate solution dropwise into Na3PO4 solution, and stir the reaction for 10 min to 15 min at a speed of 450 r / min to 500 r / min and a temperature of 60℃ to 70℃. Then, perform water bath heating reaction, cool to room temperature, wash and filter to obtain precipitate. Perform vacuum drying and grinding of precipitate to obtain NaFePO4 powder.

[0005] The beneficial effects of this invention are: This invention aims to achieve breakthroughs in environmental protection and sustainable development. By cleverly utilizing high-iron fly ash from waste materials, the iron element contained within it is converted into high-purity ferrous ammonium sulfate, providing a reliable foundation for the preparation of novel sodium iron phosphate battery materials. This process not only achieves efficient reuse of waste resources but also significantly reduces the risk of environmental pollution. Sodium iron phosphate, as a material for new energy batteries, possesses excellent electrochemical performance, including outstanding conductivity and cycle life. This not only improves the overall performance of batteries but also promises to reduce dependence on the rare metal lithium, thereby increasing sustainability in the battery manufacturing field. This innovative cathode material opens up new directions for the sustainable development of the battery industry, as detailed below: 1. Efficient utilization of resources: By utilizing the iron element in fly ash, the waste from coal mining industry is efficiently recycled, transforming the waste into new energy battery materials with practical application value.

[0006] 2. Reduced battery manufacturing costs: Sodium iron phosphate, as a cathode material for batteries, may have a relatively low cost, especially compared to the rare metal materials used in traditional lithium-ion batteries. This is expected to reduce the manufacturing cost of new energy batteries and improve their commercial competitiveness.

[0007] 3. Improve battery performance: Sodium iron phosphate has good electrochemical properties, such as high conductivity and good cycle life, which can improve the overall performance of the battery and make it more reliable in practical applications.

[0008] 4. Environmentally friendly: By reusing waste resources, it is expected to reduce the demand for raw mineral resources, reduce the impact on the environment, and conform to the concept of sustainable development and environmental protection.

[0009] 5. Potential advantages of sodium-ion batteries: Compared to lithium-ion batteries, sodium resources are relatively abundant and the cost is lower. Therefore, this specific embodiment chooses sodium ions as the battery system, which has broader application potential in new energy storage.

[0010] 6. Solution to the waste problem: By extracting and utilizing the useful elements in the waste (fly ash), this specific implementation method effectively solves the problems of waste treatment and environmental protection, and is an innovation of traditional treatment methods.

[0011] 7. The direction of sustainable development: Converting coal mine industrial waste into new energy battery materials is in line with the concept of sustainable development and promotes research and application in the fields of energy and environment.

[0012] Overall, this specific implementation method demonstrates significant effects and advantages in resource utilization, cost reduction, performance improvement, and environmental protection, representing a promising innovation in the fields of solid waste resource utilization and new energy battery materials. Compared to lithium-ion battery cathode materials, this material offers advantages such as high safety, significant application potential, abundant reserves, and low cost, making it more suitable for large-scale energy storage. Attached Figure Description

[0013] Figure 1 This invention describes the technical route for preparing sodium iron phosphate using high-iron fly ash. Figure 2 The image shows the SEM spectrum of the NaFePO4 powder prepared in Example 1. a is a scale bar of 1 μm and b is a scale bar of 10 μm. Detailed Implementation

[0014] Specific implementation method one, combined with Figure 1 Detailed explanation: This embodiment is a method for preparing sodium ferric phosphate using high-iron fly ash, which is carried out according to the following steps: 1. Mix high-speed iron fly ash with sulfuric acid, heat at 140℃~180℃ for 4h~6h, then filter and wash to obtain filtrate; ② Add sodium hydroxide solution dropwise to the filtrate to adjust the pH, and react at room temperature for 3 to 5 hours. After the reaction is complete, a reddish-brown precipitate will appear. Then filter to obtain the filter residue. ③ Add ultrapure water to the filter residue, then add sulfuric acid and iron powder. React at 60℃~80℃ for 10min~20min. Finally, filter out the excess iron powder to obtain ferrous sulfate solution. ④ Add (NH4)2SO4 to the ferrous sulfate solution to dissolve until the pH is 1~2, then evaporate and crystallize at a temperature of 90℃~110℃, and finally wash and filter to obtain ferrous ammonium sulfate. 2. Dissolve ferrous ammonium sulfate in water, then add L-ascorbic acid and stir to dissolve, thus obtaining a ferrous ammonium sulfate solution; 3. Dissolve Na3PO4 in deionized water to obtain Na3PO4 solution; 4. Add ferrous ammonium sulfate solution dropwise into Na3PO4 solution, and stir the reaction for 10 min to 15 min at a speed of 450 r / min to 500 r / min and a temperature of 60℃ to 70℃. Then, perform water bath heating reaction, cool to room temperature, wash and filter to obtain precipitate. Perform vacuum drying and grinding of precipitate to obtain NaFePO4 powder.

[0015] The technical approach of this specific implementation method is as follows: Figure 1 As shown, through a series of highly engineered processes, high-iron fly ash is cleverly converted into ferrous sulfate, which is then combined with ammonium sulfate to prepare ferrous ammonium sulfate. Finally, ferrous ammonium sulfate is used as an iron source to successfully synthesize the cathode material of a new generation of energy storage technology—sodium iron phosphate battery.

[0016] This specific implementation method represents an innovation in the engineering field of converting waste resources into high-performance battery materials. Through simplified and sustainable chemical reaction steps, it achieves efficient conversion from raw materials to the final product, providing a unique and feasible approach for the preparation of new energy battery materials. The experimental design and technical route demonstrated in this research not only have profound application prospects in the field of energy storage but also offer another viable path for sustainable development and environmental protection.

[0017] In step one of this specific implementation method, adjusting the ratio of sulfuric acid to high-iron fly ash affects the reaction efficiency and the properties of the product to some extent.

[0018] In step one of this specific implementation method, the reaction temperature and time are adjusted to achieve ideal reaction kinetics.

[0019] In step 1③ of this specific implementation method, when adding sulfuric acid, ensure chemical equilibrium and a suitable acidic environment in the reaction.

[0020] In step 1, ④ of this specific implementation method, the pH is adjusted to 1~2 to ensure that the required acid-base balance is maintained during the reaction.

[0021] In step two of this specific embodiment, the amount of ascorbic acid added is controlled during the preparation of sodium iron phosphate to maintain appropriate reduction conditions.

[0022] In step four of this specific implementation method, the temperature and time of the water bath heating reaction are controlled to ensure the quality and stability of the product.

[0023] The beneficial effects of this embodiment are: The research findings of this implementation method aim to achieve breakthroughs in the fields of environmental protection and sustainable development. By cleverly utilizing the iron-containing fly ash from waste materials, the iron element is converted into high-purity ferrous ammonium sulfate, providing a reliable foundation for the preparation of novel energy sodium iron phosphate battery materials. This process not only achieves efficient reuse of waste resources but also significantly reduces the risk of environmental pollution. Sodium iron phosphate, as a material for new energy batteries, possesses excellent electrochemical performance, including outstanding conductivity and cycle life. This not only improves the overall performance of batteries but also promises to reduce dependence on the rare metal lithium, thereby increasing sustainability in the battery manufacturing field. This innovative cathode material opens up new directions for the sustainable development of the battery industry, as detailed below: 1. Efficient utilization of resources: By utilizing the iron element in fly ash, the waste from coal mining industry is efficiently recycled, transforming the waste into new energy battery materials with practical application value.

[0024] 2. Reduced battery manufacturing costs: Sodium iron phosphate, as a cathode material for batteries, may have a relatively low cost, especially compared to the rare metal materials used in traditional lithium-ion batteries. This is expected to reduce the manufacturing cost of new energy batteries and improve their commercial competitiveness.

[0025] 3. Improve battery performance: Sodium iron phosphate has good electrochemical properties, such as high conductivity and good cycle life, which can improve the overall performance of the battery and make it more reliable in practical applications.

[0026] 4. Environmentally friendly: By reusing waste resources, it is expected to reduce the demand for raw mineral resources, reduce the impact on the environment, and conform to the concept of sustainable development and environmental protection.

[0027] 5. Potential advantages of sodium-ion batteries: Compared to lithium-ion batteries, sodium resources are relatively abundant and the cost is lower. Therefore, this specific embodiment chooses sodium ions as the battery system, which has broader application potential in new energy storage.

[0028] 6. Solution to the waste problem: By extracting and utilizing the useful elements in the waste (fly ash), this specific implementation method effectively solves the problems of waste treatment and environmental protection, and is an innovation of traditional treatment methods.

[0029] 7. The direction of sustainable development: Converting coal mine industrial waste into new energy battery materials is in line with the concept of sustainable development and promotes research and application in the fields of energy and environment.

[0030] Overall, this specific implementation method demonstrates significant effects and advantages in resource utilization, cost reduction, performance improvement, and environmental protection, representing a promising innovation in the fields of solid waste resource utilization and new energy battery materials. Compared to lithium-ion battery cathode materials, this material offers advantages such as high safety, significant application potential, abundant reserves, and low cost, making it more suitable for large-scale energy storage.

[0031] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the mass percentage of iron in the high-speed iron fly ash mentioned in step one ① is 24%~25%. Everything else is the same as in Specific Implementation Method One.

[0032] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that: the concentration of sulfuric acid in step one ① is 3 mol / L to 3.68 mol / L; the concentration of sodium hydroxide solution in step one ② is 1.5 mol / L to 2.5 mol / L; and the concentration of sulfuric acid in step one ③ is 2 mol / L to 2.5 mol / L. Everything else is the same as in Specific Implementation Method One or Two.

[0033] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in the following ways: In step one ①, the mass ratio of high-iron fly ash to sulfuric acid is 1g:(4~6)mL; in step one ③, the mass ratio of filter residue to ultrapure water is 1g:(30~32)mL; in step one ③, the mass ratio of filter residue to sulfuric acid is 1g:(2.5~6.5)mL; and in step one ③, the mass ratio of filter residue to iron powder is 1:(0.5~0.6). Everything else is the same as in Specific Implementation Methods One to Three.

[0034] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that: in step one, sodium hydroxide solution is added dropwise to the filtrate to adjust the pH to 12.5-13. Everything else is the same as in Specific Implementation Methods One to Four.

[0035] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that: the mass ratio of ferrous ammonium sulfate to water in step two is 1 g:(14~16) mL; the mass ratio of ferrous ammonium sulfate to L-ascorbic acid in step two is 1:(0.132~0.142). Everything else is the same as in Specific Implementation Methods One to Five.

[0036] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that: in step three, Na3PO4 is dissolved in deionized water at a temperature of 65℃~75℃; the concentration of Na3PO4 in the Na3PO4 solution in step three is 0.15mol / L~0.17mol / L. Everything else is the same as in Specific Implementation Methods One to Six.

[0037] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that: in step four, the ferrous ammonium sulfate solution is added dropwise to the Na3PO4 solution at a dropping rate of 5 mL / min to 6 mL / min. Everything else is the same as in Specific Implementation Methods One to Seven.

[0038] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that: the water bath heating reaction in step four is specifically carried out at a temperature of 140℃~180℃ for 5~6 hours; the vacuum drying is specifically carried out in a vacuum drying oven at a temperature of 60℃~70℃ for 10~12 hours. Everything else is the same as in Specific Implementation Methods One to Eight.

[0039] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Methods One to Nine in that the volume ratio of ferrous ammonium sulfate solution to Na3PO4 solution in step four is 1:(1~1.2). Everything else is the same as in Specific Implementation Methods One to Nine.

[0040] The beneficial effects of the present invention are verified using the following embodiments: Example

[0041] A method for preparing sodium ferric phosphate using high-iron fly ash, comprising the following steps: 1. Mix 5g of high-speed iron fly ash with 25mL of sulfuric acid with a concentration of 3.68mol / L, heat in an ultraviolet drying oven at 150℃ for 4h, then filter by vacuum pump and wash with deionized water to obtain filtrate. ② Add 2 mol / L sodium hydroxide solution to the filtrate to adjust the pH to 12.5. React at room temperature for 4 hours. After the reaction is complete, a reddish-brown precipitate appears. Then filter the precipitate by vacuum pumping with circulating water to obtain the filter residue. ③ Add 45 mL of ultrapure water to 1.47 g of filter residue, then add 4.5 mL of 2.3 mol / L sulfuric acid and 0.76 g of iron powder. React at 75 °C for 10 min. Finally, filter out the excess iron powder to obtain ferrous sulfate solution. ④ Add (NH4)2SO4 to the ferrous sulfate solution to dissolve until the pH is 2, then evaporate and crystallize at 100℃, and finally wash and filter to obtain ferrous ammonium sulfate. 2. Dissolve 2g of ferrous ammonium sulfate in 30mL of water, then add 0.264g of L-ascorbic acid and stir to dissolve, thus obtaining a ferrous ammonium sulfate solution; 3. Dissolve Na3PO4 in deionized water at 70℃ to obtain a Na3PO4 solution; the concentration of Na3PO4 in the Na3PO4 solution is 0.17 mol / L; 4. Add 30 mL of ferrous ammonium sulfate solution to 30 mL of Na3PO4 solution at a dropping rate of 5 mL / min. Stir the reaction for 15 min at a speed of 500 r / min and a temperature of 70 °C. Then react in an infrared drying oven at a temperature of 140 °C for 6 h. After cooling to room temperature, washing and filtration are performed to obtain a precipitate. Dry the precipitate in a vacuum drying oven at a temperature of 60 °C for 12 h. Finally, grind the precipitate to obtain NaFePO4 powder.

[0042] The high-speed iron fly ash mentioned in step one is a solid waste produced by Guizhou Qianxi Chemical. Due to regional differences in Guizhou, the high-speed iron fly ash uses coal with a high iron content, including 24.26% FeO3, 24.88% SiO2, 17.85% Al2O3, 8.63% CaO, 3.73% ZrO2, 3.68% TiO2, 2.34% K2O, and 14.63% other components.

[0043] Figure 2 The image shows the SEM spectrum of the NaFePO4 powder prepared in Example 1. a represents a scale bar of 1 μm, and b represents a scale bar of 10 μm. As can be seen from the image, the NaFePO4 powder exhibits a unique geometric structure, demonstrating ordered and regular arrangement at the nanoscale. The sodium iron phosphate powder exhibits a unique olivine crystal structure. Its particle size ranges from 500 nm to 900 nm, and the overall uniform grain size indicates similar crystal dimensions, ensuring a uniform structure and improving the material's stability and performance. The close-packed lattice structure helps reduce defects and voids in the material, thereby improving electrical conductivity and promoting smoother electron and ion transport. Furthermore, from the perspective of surface framework structure, sodium iron phosphate exhibits a smaller diffusion barrier, reducing the resistance encountered by ions moving within the material. This further enhances the ion migration rate.

Claims

1. A method for preparing sodium ferric phosphate using high-iron fly ash, characterized in that... It is done in the following steps:

1. Mix 5g of high-speed iron fly ash with 25mL of sulfuric acid with a concentration of 3.68mol / L, heat in an ultraviolet drying oven at 150℃ for 4h, then filter by vacuum pump and wash with deionized water to obtain filtrate. The high-speed iron fly ash contains 24.26% Fe2O3, 24.88% SiO2, 17.85% Al2O3, 8.63% CaO, 3.73% ZrO2, 3.68% TiO2, 2.34% K2O, and 14.63% other components. ② Add 2 mol / L sodium hydroxide solution to the filtrate to adjust the pH to 12.

5. React at room temperature for 4 hours. After the reaction is complete, a reddish-brown precipitate appears. Then filter the precipitate by vacuum pumping with circulating water to obtain the filter residue. ③ Add 45 mL of ultrapure water to 1.47 g of filter residue, then add 4.5 mL of 2.3 mol / L sulfuric acid and 0.76 g of iron powder. React at 75 °C for 10 min. Finally, filter out the excess iron powder to obtain ferrous sulfate solution. ④ Add (NH4)2SO4 to the ferrous sulfate solution to dissolve until the pH is 2, then evaporate and crystallize at 100℃, and finally wash and filter to obtain ferrous ammonium sulfate.

2. Dissolve 2g of ferrous ammonium sulfate in 30mL of water, then add 0.264g of L-ascorbic acid and stir to dissolve, thus obtaining a ferrous ammonium sulfate solution; 3. Dissolve Na3PO4 in deionized water at 70℃ to obtain a Na3PO4 solution; the concentration of Na3PO4 in the Na3PO4 solution is 0.17 mol / L; 4. Add 30 mL of ferrous ammonium sulfate solution to 30 mL of Na3PO4 solution at a dropping rate of 5 mL / min. Stir the reaction for 15 min at a speed of 500 r / min and a temperature of 70 °C. Then react in an infrared drying oven at a temperature of 140 °C for 6 h. After cooling to room temperature, washing and filtration are performed to obtain a precipitate. Dry the precipitate in a vacuum drying oven at a temperature of 60 °C for 12 h. Finally, grind the precipitate to obtain NaFePO4 powder. The particle size of the sodium iron phosphate is 500nm~900nm.

Citation Information

Patent Citations

  • Graphene oxide-sodium ferric phosphate composite positive electrode material and preparation method thereof

    CN114975927A